Pengaruh kepemimpinan transformasional, lingkungan kerja fisik dan stres kerja terhadap kinerja pegawai pada kantor kecamatan penjaringan jakarta utara - Soelton, Mochamad; Yasinta, Dian (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
This research aims to know the influence of transformational leadership, physical work environment and work stress employee performance in Kantor Kecamatan Penjaringan North Jakarta. The object for this research is employee at Kantor Kecamatan Penjaringan North Jakarta. This research was done to 70 respondents by using quantitative descriptive approach. This data analysis which is used is statistic analysis in the form of double linear regression test. The results of this study indicate that partially and simultaneously variable transformational leadership, physical work environment simultaneously have a positive and significant effect on employee performance, job stress has a negative but not significant effect on employee performance on Kantor Kecamatan Penjaringan North Jakarta. It has been the result of (t) patial shows significant pont of three independent variables that supports hipothesy. Therefore the test results of this study states that there is a simultaneous influence between transformational leadership variables, physical work environment and job stress on employee performance at Kantor Kecamatan Penjaringan North Jakarta.